العوامل المؤثرة في تطبيق برنامج جودة الخدمة الصحية - د. نوال يونس محمد; د. نبال يونس محمد (PROSPECTIVE RESEARCHES, 2023)
This study adopted some effective Factors in applying the program of medical service quality such as: commitment of higher leadership with medical service quality, provision of material and human requirements, changes resisted by the employees of hospitals, higher leadership has medical information systems in order to present medical services that represent the base of a Fit program of service quality. These systems have been applied in two samples. The First sample of governmental hospitals (amounted 40 employees) included Al-Salam and Al-A'am Hospitals. The second one of non-governmental hospitals (amounted 40 employees) included Al-Zahrawi and Ninaveh hospitals. The present study was based on a hypothetical pattern depended on the Following basic hypothesis: "There are many statistically significant differences between the governmental and non-governmental hospitals with respect to relative significance of effective Factors variables in applying the program of medical service quality according the way that indicates the difference of medical service quality among them. Pattern and hypothesis of study were chosen by using statistical manner such as difference analysis in order to determine the comparison, F-test and mathematical averages in order to describe the effective Factors. Study Conclusions: The analysis results showed that there are significant differences between governmental and non-governmental hospitals in three of the Four effective Factors composing the program of service quality. Study Recommendations.